BOJONG RANGKAS GO DIGITAL: EMPOWERING BAG ARTISANS THROUGH MSME PERSONA STRATEGY AND USER GENERATED CONTENT (UGC) - Muniroh, Leny; Pasaribu, Popy Novita; Riany, Desmy; Wulandari, Berlina; Ferdiansyah, Erlangga; Natasya, Keysa Alfiani; Rahman, Azka Fadilah; Az-Zahra, Shasie Fatwa (LPPM Univ. Ibn Khaldun Bogor, 2025)
The Bojong Rangkas Go Digital program was implemented as a community empowerment initiative for bag craftsmen SMEs in Bojong Rangkas Village, Ciampea District, Bogor Regency, who face limitations in digital marketing. Although these SMEs have stable production capacity, most still rely on conventional sales methods due to low digital literacy and the absence of strong brand identity strategies. To address these challenges, the program adopted a participatory approach through digital literacy training, the development of SME persona strategies, and the utilization of User Generated Content (UGC) by the local community. The activities were conducted in September 2025, involving 18 SME partners, students as facilitators, and local communities as digital content supporters. The results showed significant improvement in the use of social media as a promotional tool, with all SMEs successfully creating or optimizing their business accounts. The craftsmen were also able to produce simple product photos and videos, and compose promotional narratives aligned with their brand identities. Furthermore, the involvement of the local community in generating UGC expanded the marketing reach and increased consumer engagement. In conclusion, the combination of digital literacy, SME persona strategies, and UGC proved effective in strengthening the competitiveness of Bojong Rangkas bag SMEs. This program not only enhanced the technical skills of craftsmen but also fostered the creation of a sustainable community-based digital marketing ecosystem.